A compact and Ultra-sensitive microfiber based interferometer sensor for precise electrical current detection - Guoyu Li; Fei Xie; Yan Li; Hongtao Li; Rui Liu; Ao Wang; Lili Liang (Results in Optics)
Precision measurement of microcurrents enhances microscopic understanding and provides accurate data for fields like research, healthcare, semiconductors, and sensors. A novel fiber-optic electrical current sensor, featuring a synchronized fusion and tapering process for integrating single-mode optical fibers with silicon microtube filled with carbon fibers, has been presented in this work. The composite waveguide structure composed of optical microfiber and silicon micro-tube forms a mode interferometer, which is with high temperature sensitivity of 8.06 nm/℃. As electrical current flows through the conductive material of carbon fiber, it generates a thermal effect, causing a temperature change around the waveguide structure and leading to a wavelength shift in the interferometer’s transmission spectrum. The magnitude of this wavelength shift directly indicates the current intensity, providing a highly sensitive approach to current sensing. Notably, our interferometer, with its compactness, remarkable sensitivity of 3625 nm/mA2, and broad measurement range spanning from 0 mA to 200 mA with a micro-current resolution of 0.002 mA, is positioned as a promising candidate for precise and reliable electrical current measurements in micro current flow detection.